Case History: Chile - One Nation Where Nationalism And Foreign Investment Are Reconciled - Eric N. Baklanoff (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1968)
A major problem whose importance touches the entire underdeveloped world is how to reconcile the demands of nationalism with the requirements of the international economy. Chile's copper industry presents a study of how one such accommodation has been slowly, if precariously, evolved. The dependence of a low-income country on the international economy presents, on the one hand, opportunities for speeding up the rate of development and, on the other, imposes a set of constraints on national behavior. Nationalism may be indispensable in motivating low-income countries to bear the economic costs and absorb the social changes involved in modernization, but it may also inhibit the acceleration of economic growth by its failure to come to terms with the international economy. Nationalism is a two-edged sword. An outstanding feature of Chile's economy since the mid-1920s has been its considerable dependence on the export of a single primary commodity- copper. Moreover, the affiliates of two US.-owned firms-the Anaconda Co. and the Kennecott Copper Corp.-have dominated Chile's copper industry, a fact which from time to time has posed conflict between that nation's long-range economic opportunities and more immediate political realities.